Model Pendidikan Life Skill Belajar Mandiri Untuk Meningkatkan Penguasaan Teknik Vokal Mahasiswa Peserta Mata Kuliah Vokal 3 - Latifah, Diah; Milyartini, Rita (INVOTEC, 2010)
The ability to learn independently, is one of life skills that need to be owned by the students as future professionals in the field of education. A professional music educator is required to be able to sing well. Mastery of singing competence can not be separated from competencies to learn independently. This study focuses on Independent Learning Ability Development Model to improve student mastery of Vocal Technique Participants. The research method is conducted using class action research. Due to time constraints the research application of the learning model can only be observed in one cycle. The results showed that the application of learning models provide a positive implication on the ability to perform self-evaluation which is considered as part of independent learning skills.